Upaya Pertumbuhan Jemaat Melalui Model Penginjilan Dan Strategi Entreperneurship Dalam Pelayanan Holistik Di Gereja Protestan Persekutuan (GPP) Maranatha - Liego Hasudungan Sianturi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The GPP Maranatha congregation is a congregation that has a majority of farmers. At this time, many congregations are experiencing difficulties in managing congregational businesses, especially in the agricultural sector, many congregations are having difficulty getting fertilizer. According to the author's observations, this is due to the increasing price of fertilizer, in this case the church needs to pay attention to the congregation. The method used by researchers is a qualitative descriptive approach. The research implementation uses procedures that produce descriptive data in the form of written and spoken words from people whose behavior can be observed through interviews or observations using a qualitative approach. This research aims to determine congregation growth efforts through evangelism models and entrepreneurship strategies in holistic services at the Maranatha Fellowship Protestant Church (GPP). From the results of the research, it can be seen that the efforts that must be made by the church to help increase the growth of the congregation both spiritually and physically are: providing assistance to the congregation such as: the church re-holding Communion that was previously held by the congregation at the Maranatha Fellowship Protestant Church (GPP), The church made visits to the congregation and the church provided training in making liquid fertilizer and provided livestock business. With this assistance, the congregation at the Maranatha United Protestant Church (GPP) will experience development